2019
DOI: 10.1007/s10450-019-00153-y
|View full text |Cite
|
Sign up to set email alerts
|

Copper-exchanged Y zeolites for gasoline deep-desulfurization

Abstract: Adsorptive desulfurization is one of the most efficient methods to remove recalcitrant sulfur compounds from transportation fuels. Two π-complexation-based sorbents were studied for desulfurization of synthetic gasoline. The sorbents were obtained by ion exchanging Y zeolites with copper cations using different techniques, which includes liquid phase ion exchange (CuY1) and vapor phase ion exchange (CuY2). Preliminary kinetic and equilibrium experiments for sulfur adsorption in batch system showed that CuY1 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Copper-containing zeolites are an extensively studied class of materials with various potential applications. These materials are industrially implemented as the “DeNOx” catalysts for the direct decomposition of nitrogen oxides or their selective catalytic reduction (SCR) with ammonia and hydrocarbons. , They may be used as the efficient adsorbents for the fuel desulphurization due to selective binding of thiophenic compounds. Recently, the possibility to selectively oxidize methane to methanol via the chemical looping over copper-containing zeolites was demonstrated, hence opening the broad opportunities for the effective utilization of natural gas at remote oil mines.…”
Section: Introductionmentioning
confidence: 99%
“…Copper-containing zeolites are an extensively studied class of materials with various potential applications. These materials are industrially implemented as the “DeNOx” catalysts for the direct decomposition of nitrogen oxides or their selective catalytic reduction (SCR) with ammonia and hydrocarbons. , They may be used as the efficient adsorbents for the fuel desulphurization due to selective binding of thiophenic compounds. Recently, the possibility to selectively oxidize methane to methanol via the chemical looping over copper-containing zeolites was demonstrated, hence opening the broad opportunities for the effective utilization of natural gas at remote oil mines.…”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal-containing zeolites belong to an important class of materials widely used as adsorbents and catalysts for various chemical transformations. , Among them, copper-containing zeolites have been studied in depth due to their great adsorption capacity for fuel desulphurization, high catalytic activity in the decomposition of nitrogen oxides, and selective catalytic reduction (SCR). The recent discovery of the selective methane oxidation to methanol over copper-containing zeolites based on the chemical looping approach brought about new opportunities for utilizing these materials for the effective valorization of natural gas.…”
Section: Introductionmentioning
confidence: 99%
“…Myriam et al. [ 13 ] used copper exchange Y zeolite (CuY) to remove thiophene from synthetic gasoline at room temperature. Kevin [ 14 ] prepared Ce and Cu ion‐exchange mesoporous Y zeolite for the adsorption and removal of sulfur compounds in liquid fuels, and found that it has a broad application prospect in the selective removal of sulfur compounds.…”
Section: Introductionmentioning
confidence: 99%